Extreme electric fields power catalysis in the active site of ketosteroid isomerase - Fried, Stephen D. (Science, 2014)
Enzymes use protein architecture to impose specific electrostatic fields onto their bound substrates, but the magnitude and catalytic effect of these electric fields have proven difficult to quantify with standard experimental approaches. Using vibrational Stark effect spectroscopy, we found that the active site of the enzyme ketosteroid isomerase (KSI) exerts an extremely large electric field onto the C=O chemical bond that undergoes a charge rearrangement in KSI’s rate-determining step. Moreover, we found that the magnitude of the electric field exerted by the active site strongly correlates with the enzyme’s catalytic rate enhancement, enabling us to quantify the fraction of the catalytic effect that is electrostatic in origin. The measurements described here may help explain the role of electrostatics in many other enzymes and biomolecular systems.